Phillips’s points and Padmapāda’s possible defense - Guha N. (My University, 2025)
In an article entitled “Padmapāda’s Illusion Argument,” Prof. Stephen Phillips argues that Padmapāda failed to show the possibility of his views about the absolute (brahman) through his illusion argument. Phillips, like many other philosophers, criticized the arguments Padmapāda presented in his Pañca-pādikā. This chapter will try to extract Padmapāda’s arguments from his writings and address the issues raised by Phillips. Although those arguments originated in the writings of Padmapāda, they have their own lives. They evolved through various other commentarial and independent philosophical works. The fundamental and subtle questions or issues Phillips has raised may not find answers in Pañca-pādikā. But one may address those issues by using the ideas which Phillips calls “Padmapāda’s arguments.” © 2024 selection and editorial matter, Malcolm Keating and Matthew R. Dasti; individual chapters, the contributors.